Interpretação transemiótica de práticas sociolinguísticas expressas em português escrito por pessoas surdas - Lima, Hildomar José de (2020)
This research aims to reflect on the sociolinguistic practices expressed in written Portuguese by deaf people and, from that, to problematize the colonial linguistic conceptions and the ideologies underlying the exercise of power, through language, over historically subordinated linguistic communities, specifically the deaf community. We start with the assumption that the production of meaning in the text written in Portuguese by the deaf person emerges from the sociolinguistic crossing between sign languages and oral languages, that is, in a context of translinguaging (sociolinguistic crossing between languages) and transmodality (sociolinguistic crossing between languages of different modalities) (LIMA; REZENDE, 2019b). The empirical materiality of this research is formed by texts written in Portuguese by deaf people who participated in the selection process for the course of Licenciatura em Letras: Libras, at the Universidade Federal de Goiás, between 2010 and 2018. This research is part of the decoloniality field of study, since questions about linguistic policies that place deaf people in the web of coloniality of power (QUIJANO, 2009; 2005; 2000), knowledge (LANDER, 2005) and language (GARCÉS, 2007) are especially problematized. The epistemological path of the discussion starts from the problematization of the interlanguage as a theoretical perspective that directs researches that propose to study written practices expressed in Portuguese by the deaf people. In general, what is observed in the interlanguage, as a theoretical foundation, is a historical-epistemic view that the written Portuguese of the deaf person is a system made incomplete and deficient by the interference of the deaf person's first language, the libras. In this study, transemiotics is proposed as an interpretative method of sociolinguistic practices expressed in Portuguese written by deaf people as an alternative to interlanguage, which represents a sociolinguistic prison for the deaf person in in the form of an incomplete and deficient Portuguese. Three issues were observed that permeate transemiotic interpretation. In the first one, onto and epistemological dimensions of the deaf being in transemiotic interpretation, we discuss the deaf body, which is human and political, as a locus for the construction of meaning in the written production of Portuguese by the deaf person. In the second one, euro-listenism and ontoepistemicide, we approach ontoepistemicide, which in the context of this research means any and all forms of violence, be it symbolic or physical, against the deaf way of being and living in the world, as a consequence of crossing the deaf body by euro-listenism and how that it reflected in the language of the deaf person. In the third, transemiotic interpretation and social repositioning through the deaf narrative, we shown how the deaf person's written language as it is, in the way it is reflected in a confrontation that socially reposition the deaf person from the place of “abnormality” / “incapacity” (subordination) to the place of “normality” / “capacity”. Among the contributions of this research is the theoretical and political confrontation important to weaken the prejudiced and discriminatory positions of monolingual mentalities in Brazil and, from that, create and strengthen linguistic policies that promote attitudes of valorization of all languages, of the different sociolinguistic practices of the Portuguese and, consequently, the understanding of all peoples, in their differences.